Western diet-induced mouse model of non-alcoholic fatty liver disease associated with metabolic outcomes: Features of gut microbiome–liver–adipose tissue axis - Romualdo, Guilherme R. [UNESP]; Valente, Letícia Cardoso [UNESP]; Sprocatti, Ana Carolina [UNESP]; Bacil, Gabriel Prata [UNESP]; de Souza, Isadora Penedo [UNESP]; Rodrigues, Josias [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Vinken, Mathieu; Cogliati, Bruno; Barbisan, Luís Fernando [UNESP] (Elsevier, 2022)
Objectives: Non-alcoholic fatty liver disease (NAFLD) has a growing epidemiologic and economic burden. It is associated with Western diet (WD) patterns, and its pathogenesis involves metabolic disorders (obesity, dyslipidemia, hyperglycemia, and diabetes) and gut dysbiosis, features that are usually neglected or not reproduced by most animal models. Thus, we established a 6-mo WD-induced NAFLD mouse model associated with metabolic disorder, investigating its main features at the gut microbiome–liver-adipose tissue axis, also evaluating the correlations of gut dysbiosis to the other disease outcomes. Methods: Male C57 BL6 mice received a high-fat (30% lard and 0.2% cholesterol, ∼57% calories) and sucrose-rich (20%) chow, and a high-sugar solution (23.1 and 18.9 g/L of D-fructose and D-glucose) for 6 mo. Results: The model featured high serum cholesterol levels, glucose intolerance, and hyperinsulinemia. WD intervention resulted in extensive macro/microvesicular liver steatosis and pericellular fibrosis—resembling human disease—accompanied by hepatic stellate cell activation and CD68+ macrophage infiltration, increased protein levels of proinflammatory p65-nuclear factor-κB, interleukin-6 and tumor necrosis factor-α, with decreased antioxidant regulator Nrf2. Mice showed clear obesity with adipocyte hypertrophy, and CD68+macrophage/mast cell infiltration in adipose tissue while a reduction in number of goblet cells was also observed in the small intestine. Moreover, the pyrosequencing of the 16 S ribosomal RNA of gut cecal content showed decreased bacterial diversity, enriched Firmicutes and Proteobacteria, decreased Bacteroidetes and Fusobacteria, and increased ratio of Firmicutes to Bacteroidetes. Bacteroidetes and Bacteroides had the highest number of significant correlations with liver–adipose tissue axis outcomes. In silico analysis of gut microbiome in NAFLD obese patients revealed a depletion in Bacteroides, which also correlated to disease outcomes. Conclusion: This mice model gathered suitable phenotypical alterations in gut–liver–adipose tissue axis that resembled NAFLD associated with metabolic disorders in humans and may be considered for preclinical investigation.
Keywords: Adipose tissue; Liver steatosis and fibrosis; Microbiome; Non-alcoholic fatty liver disease; Non-alcoholic steatohepatitis; Western diet